PERBEDAAN PERSEPSI AKUNTAN PUBLIK, AKUNTAN PENDIDIK, DAN MAHASISWA AKUNTANSI TERHADAP KODE ETIK IKATAN AKUNTAN INDONESIA - Widyawati, Widyawati; Ika S, Ardiani (JURNAL AKUNTANSI UNIVERSITAS JEMBER, 2011)
Accounting profession should always act with due observance of professional ethics IAI. How far the accounting profession in upholding the ethical code of practice will be looked at do. Because of the better practices conducted by the accountant in the performance of duties, then the better the perception that the code of ethics will be presented to the IAI. And knowledge of ethics is the foundation for the accountants to behave ethically or not. In addition, accounting education major effect on ethical behavior of accountants. This study aims to determine differences in perceptions of the Code of Ethics for Public Accountants, Accounting Educators, and Student Accounting. The population in the study year 2010 is all public accountant who worked at Public Accounting Firm (KAP) in Semarang, Accounting educators and students of accounting at the University of particularly public and private schools are UNIKA, Diponegoro University, and UNISULLA. The samples totaling 164 people, consisting of 54 public accountants, 27 accountants accounting educators and 83 students. The variable in this study is persepsi public accountant (XI), accounting educators (X2), and accounting students (X3) to the code of conduct based on ethical principles and rules of ethical accounting profession compartment in the code of ethics of public accountants IAI. Data analysis method was used to test the quality of data that include test validity, test reliability, test the classical assumption. Results of research by descriptive analysis showed that the percentage of the average public accountants, educators and students of accounting akuntan equally positive thinking, both to the principles of professional ethics of accountants and public accountants compartment ethics rules in the code of ethics IAI. The hypothesis test results for the first hypothesis can be seen that Sign value 0.000